2001
DOI: 10.1046/j.1440-1681.2001.03527.x
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Inhibits Development Of Atherosclerotic Lesions In apolipoprotein E‐Deficient Mice

Abstract: 1. The effects of taurine on the development of atherosclerotic lesions were investigated in apolipoprotein (apo) E-deficient mice, an animal model with severe hypercholesterolaemia and extensive atherosclerosis. These mice were fed a normal laboratory chow containing 2% taurine for 12 weeks. 2. Serum total cholesterol was significantly elevated after 12 weeks treatment with taurine. This elevation was due to increases in very low-density lipoprotein- and low-density lipoprotein-cholesterol. 3. Despite such ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
(84 reference statements)
4
19
0
Order By: Relevance
“…However, in these earlier studies, the effects of high plasma cholesterol on the development of aortic atherosclerosis, as described in this study, have been previously investigated using alternate approaches, such as the oil-red O technique. 18,19 However, these en face preparations of tissue do not allow for the volumetric quantification of plaque or the encroachment on the lumen, nor do they detect intimal proliferation. Other investigators have quantitated atherosclerosis formation in paraffin-embedded sections, although this method of processing causes variable degrees of tissue shrinkage and thus complicates the interpretation of the end results.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these earlier studies, the effects of high plasma cholesterol on the development of aortic atherosclerosis, as described in this study, have been previously investigated using alternate approaches, such as the oil-red O technique. 18,19 However, these en face preparations of tissue do not allow for the volumetric quantification of plaque or the encroachment on the lumen, nor do they detect intimal proliferation. Other investigators have quantitated atherosclerosis formation in paraffin-embedded sections, although this method of processing causes variable degrees of tissue shrinkage and thus complicates the interpretation of the end results.…”
Section: Discussionmentioning
confidence: 99%
“…10,17,18) On the other hand, there is no information in the literature as to whether taurine has any regressive effect on existing atherosclerotic lesions and oxidative stress in experimental animals fed on an HC diet. However, a taurine treatment has been observed to decrease existing aortic lesions and lipid accumulation, as well as lipid peroxide levels in the plasma and aorta without affecting the plasma cholesterol levels in apo-E deficient mice, 19) spontaneously hyperlipidaemic (SHL) mice 20) and Watanabe heritable hyperlipidemic (WHLL) rabbits, 21) all animal models with severe hypercholesterolemia and extensive atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sethupathy et al (22) demonstrated that the oxidant activity, measured by thiobarbituric acid reactive substances (TBARS), was significantly less in the plasma of male Wistar rats fed a high-fat diet supplemented with 50 mg/kg/ day taurine for six months (1.6 nmol/mL) compared to rats fed a high-fat diet without taurine supplementation (2.4 nmol/mL). Serum TBARS were also significantly lowered in apolipoprotein E-deficient mice after 2% taurine supplementation for 12 weeks (8.6 nmol/mL), compared to mice without taurine supplementation (11.1 nmol/mL) (13). Taurine is also known to react with hypochlorous acid (HOCl), a powerful oxidant, to create a more stable taurine chloramine (TauCl) in vivo to block the production of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%